Pengaruh Asam Humat terhadap Karakteristik Morfologi Tebu (Saccharum officinarum L.) Varietas Bululawang - Lubis, Faizal Anam Al Ubaidah; Pamungkas, Saktiyono Sigit Tri; Sukmawati, Fitria Nugraheni (Jurnal Agro Industri Perkebunan, 2022)
Sugarcane (Saccharum officinarum L.) is a plantation crop that is used as raw material for the consumer sugar and industrial sugar. The need for sugar is increasing every year but is not matched by an increase in sugarcane production due to several factors including cultivation management that is not optimal. Sugarcane production begins with good nursery management, including using genetic of seeds and the right planting media. One alternative to improve the quality of growing media is to use humic acid (HA) as a soil enhancer. This study aims to determinate the effect of giving HA on the morphological characteristics of sugarcane seedlings of Bululawang variety (BL). This research was carried out in an integrated laboratory greenhouse at the Polytechnic LPP Yogyakarta from Maret to July 2021. This study used a non-factorial completely randomized design (CRD) with five treatments and three replications consisting of P0 (control), P1 (25 ml.polybag-1), P2 (50 ml.polybag-1), P3 (75 ml.polybag-1), and P4 (100 ml.polybag-1). The morphological characteristics observed is plants height (cm), number of leaves (strands), stem diameter (mm) and longest root length (cm). the results of the study were analyzed using ANOVA at the 5% level and continued using the Duncan Multiple Range Test (DMRT) at the 5% level. The result showed the effect on morphological characters on all observation variables where the P3 treatment had the best growth and morphological characters, so that in general the additional of HA affected the morphological characteristics of sugarcane seedlings of BL varieties.